Representations and discourses in internet comedy [a review of www.9gag.com] - Gutierrez, Jose C., III (2015)
Access online through this link: https://www.plarideljournal.org/article/representations-and-discourses-in-internet-comedy
Keywords: 9gag.com (Website); Internet entertainment; Comedy